Estudo da Atividade Hipotensora das Folhas de Syzygium jambolanum D.C. (jambolão) - Ribeiro, Rachel Melo (2007)
This work was carried out to evaluate the effect of sheets of Syzygium jambolanum DC (jambolan) in blood pressure (BP) and reactivity of vascular smooth muscle and non-vascular of normotensive rats. The extract hidroalcóolico (EH; ethanol 70%) was obtained by maceration from the dried leaves of Syzygium jambolanum DC to evaluate blood pressure in conscious rats and preparations isolated from deferent duct or thoracic aorta of rats. The EH was submitted the division with solvent using chloroform / water (2:1 v / v) to obtain the fractions chloroform (FC) and water (FMD) and assessment of vascular reactivity-ring mesenteric artery. The oral administration of EH (0.1 g / kg / day or 0.2 g / kg / day) induced a significant reduction of the PA in rats with normal conscious. In preparations of duct deferentes isolated from rats, EH 0.05, 0.1 and 0.25 mg / ml reduced the effect maximum (Emax) induced by norepinephrine (NE) at 22.2, 45.4 and 81.5%, respectively. In ducts deferentes previously contracted with the CE75% noradrenaline (3x10-4 M) the EH (0.2 to 14 mg / ml) induced relaxation, dependent on concentration, which reached 69%, with the largest concentration. In arteries aorta thoracic isolated from rats, EH 0025, 0.05 and 0.1 mg / ml moved to the right, the cumulative concentration-response curves of calcium (Ca + +) at 7.7, 2.8 and 5.2 times, respectively. This effect of EH was accompanied by a reduction in the Emax 30.5; 56.4 and 78.4% respectively. The FA (0.1, 0.25 and 0.5 mg / ml) reduced the effect maximum (Emax) of 6.5 in NE, 15.7 and 51.9% visited the curve to the right in 2.0, 2.8 and 3.5 times respectively. The FC 0.5 mg / ml reduced the Emax of 25.8% in NE. The FC (0.1 and 0.25 mg / ml) reduced the Emax of concentration-response curve cumulative calcium (Ca + +) at 21.1 and 47.1% and moved to right on 3 and 4 times, respectively. In addition, the FC (0.01 to 1.0 mg / ml) induced relaxation, dependent on concentration, mesenteric artery pre-contracted with calcium (≅ EC75), the maximum concentration (1mg/ml), in the absence or presence of the blocker of potassium channels (Tetraetilamônio-TEA), 97.4 and 99.6% respectively. Together, these results suggest that the effect of lowering the EH Syzygium DC can jambolanum be related to activity relaxing blood presented by the FC in rings of artery mesenteric pre-contracted with calcium. Thus this work contributes to hypotensive confirmation of the activity of the leaves of Syzygium jambolanum DC Maranhão employed by the population.